Factors influencing the use of the “truth in sentencing” law in Kentucky murder cases: A research note - Keil, Thomas J. (American journal of criminal justice, 1995)
This study is based upon a data set on the capital sentencing process in Kentucky. Here, we examine the effect of Kentucky’s “truth in sentencing” statute on murder cases. The evidence suggests that a sentence of life without possibility of parole can serve as an alternative to capital sentencing that avoids racial discrimination.